Encouraging Rural Engagement of Young People: Understanding Career Choices of Students in the Agribusiness Sector - Pranvera Troka; Amalia Tola; Jonida Avdulaj; Marsela Luarasi; Klea Nika (European Scientific Journal, ESJ, 2024)
Agriculture is one of the main economic sectors in Albania, contributing to about 20% of the GDP and about 45% of the employment opportunities. The high rate of youth migration represents a threat to the future and sustainability of the agriculture sector. The purpose of this paper is to identify the factors that influence the career choice of young people in terms of rural engagement and explore the challenges that hinder them from selecting agriculture as their career path. This paper focuses on the students of the Faculty of Economy and Agribusiness at the Agricultural University of Tirana (AUT), as agribusiness is a closely related field to agriculture. The results show that employment opportunities, personal interest in the field, and financial prospects are the main factors that motivate students to choose a study program in agribusiness. However, other factors such as a positive perception of agriculture, participation in internship programs and extracurricular activities, or career consulting from the university influence students to engage and retain in agriculture and related fields. This study provides valuable data to formulate and develop strategies for attracting students in the agriculture sector.